Congestion control of TCP over heterogenous networks - Zhan, Zhuoqun (2008)
Improving TCP performance over wireless network by taking into consideration both the random transmission error and handoff on wireless links. The new scheme adds a software agent in the base station and maintains the end-to-end TCP semantics. This would be transparent to both TCP sender and receiver.